1986
DOI: 10.1203/00006450-198609000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Selective Elevation of Systemic Blood Pressure by Epinephrine during Sepsis-Induced Pulmonary Hypertension in Piglets

Abstract: ABSTRACT. In a piglet model of group B fi Streptococci SVI, stroke volume index (GBS)-induced pulmonary hypertension, we have deter-CVP, central venous pressure mined hemodynamic responses to epinephrine (EPI) infusion in both the systemic and pulmonary circulations.Three groups of piglets (GBS + EPI, n = 6; GBS + ~lacebo. n = 6: ~lacebo. n = 6 ) were studied. GBS, infused intravenously -5 x l~~' o r~a n i s m s / k~/ m i n , 'reduced cardiac index and stroke volume index while elevating pulmonary artery press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…Previously, EP has been shown to have variable effects on the pulmonary vasculature. Consistent with our findings, other investigators have reported a significant decrease in PVR during EP infusion in piglets (29,30). Doses in these studies ranged from 0.2 to 15 g/kg/min.…”
Section: Catecholamine Administrationsupporting
confidence: 81%
“…Previously, EP has been shown to have variable effects on the pulmonary vasculature. Consistent with our findings, other investigators have reported a significant decrease in PVR during EP infusion in piglets (29,30). Doses in these studies ranged from 0.2 to 15 g/kg/min.…”
Section: Catecholamine Administrationsupporting
confidence: 81%
“…However this approach has not yet been systematically investigated. The data of Meadow et al (3) for the newborn pig suggest that large doses are necessary to accomplish a significant increase in systemic vascular resistance. In their study, a significant increase in Qp was observed during administration of as much as 15 pg/kg/min of epinephrine, a dose much greater than presently recommended for use in newborn infants (8).…”
Section: Discussionmentioning
confidence: 98%
“…Meadow et al (3) reported that after group B streptococcusinduced pulmonary hypertension in the piglet, a significant increase in Qp can be achieved by elevating the PSA Although not evaluated in their experimental animals, Meadow et al also suggested that a selective elevation of the PsA during pulmonary hypertension could also impede right to left shunt at the foramen ovale and thus improve oxygenation (3). Furthermore, in adult animals with RVH and decreased Qp, an elevation in PSA increases cardiac output (4)(5)(6).…”
mentioning
confidence: 99%
“…(3). We can thus compare the results of our high-dose infusions with the lowest dose used in their study.…”
Section: Discussionmentioning
confidence: 99%